Incentives and risk-sharing in public procurement of innovations: Towards contracting strategy framework. Issue 2 (3rd June 2019) - Suhonen, Niko; Tammi, Timo; Saastamoinen, Jani; Pesu, Jarkko; Turtiainen, Matti; Okkonen, Lasse
Abstract : Purpose: Public procurement of innovations (PPIs) addresses a specified need of the public-sector customer or aims at fostering private firms' innovativeness. In an operational sense, issues of information asymmetry and risk sharing between the public agency and the supplier are of paramount importance. The purpose of this paper is to focus on the contract design issues of PPI. Design/methodology/approach: Explicit and implicit contracting methods are reviewed, and a conceptual framework is proposed in which procurement characteristics are analyzed, focusing on the dimensions of the supplier's sensitivity to the procurement risk and the power of implicit contracting methods. Findings: Because of its complex nature, applying cost-plus contracts instead of more common fixed-price contracts is advisable in PPI. Originality/value: Possible reasons for the more prominent role of contract design in the USA as opposed to the European Union procurement are discussed.